2013
DOI: 10.1111/1467-8268.12059
|View full text |Cite
|
Sign up to set email alerts
|

Credit Constraints and Agricultural Risk for Non‐Farm Enterprises

Abstract: This paper uses two nationally representative datasets collected in 1992 and 2003 in Gambia to analyse small, nonfarm enterprises. The results reveal evidence of significant credit constraint among these non-farm enterprises. Specifically, household wealth is a significant determinant not only of entry into the enterprise sector but also determines investment levels conditional upon entry. Furthermore, the marginal returns to investments in enterprises are very high and significantly exceed the prevailing lend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Jerome (2011) points out that access to infrastructure enables people to take part in productive activities that accelerate poverty reduction. Gajigo and Lukoma (2011) argue that investment in infrastructure can have direct and indirect benefits for poor people. The authors add that rural infrastructure (especially roads and irrigation) promotes agricultural development, which raises the real income of farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jerome (2011) points out that access to infrastructure enables people to take part in productive activities that accelerate poverty reduction. Gajigo and Lukoma (2011) argue that investment in infrastructure can have direct and indirect benefits for poor people. The authors add that rural infrastructure (especially roads and irrigation) promotes agricultural development, which raises the real income of farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past studies have shown that access to finance can have a direct impact on rural youth entrepreneurship (Ullah, 2020;Liu et al, 2019) and plays an important role in inclusive rural transformation by facilitating farm households' entrepreneurial activities. From the entrepreneurship theory, many factors including individual traits and characteristics, firm's characteristics as well as business environment determine the creation and the performance of a firm (Gajigo, 2013;Baye, 2013, Gartner, 1985.…”
Section: Conceptual and Empirical Frameworkmentioning
confidence: 99%
“…Key success factors in diversified rural non-farm enterprises include education, set skills, financial capital and socio-economics (Davis, 2016;Winters et al, 2011), good infrastructure and transport (Senadza, 2012), communication and information technology and market access (Gajigo, 2013). Many rural people neither own nor have access to these and encounter many challenges in their struggle to maintain decent livelihoods.…”
Section: Empirical Reviewmentioning
confidence: 99%